The Information in Long-Maturity Forward Rates - Fama, Eugene F.; Bliss, Robert R. (American Economic Review, 1987)
Current 1 -year forward rates on 1 - to 5-year U.S. Treasury bonds are information about the current term structure of 1-year expected returns on the bonds, and forward rates track variation through time in 1-year expected returns. More interesting, 1 -year forward rates forecast changes in the 1 -year interest rate 2- to l-years ahead, and forecast power increases with the forecast horizon. We attribute this forecast power to a mean-reverting tendency in the 1-year interest rate